Principal’s Strategic Efforts in Enhancing Teacher Performance Through Effective Implementation of Educational Supervision at SDI Puudhombo Elementary School - Hildegardis Mbao Buro; Skolastika Lelu Beding; Alfonsus Mudi Aran (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This qualitative descriptive research explores the principal’s efforts to enhance teacher performance through the implementation of educational supervision at SDI Puudhombo, East Nusa Tenggara. The study aims to understand the strategies, processes, and impacts of educational supervision in improving teaching quality. Purposive sampling was used to select three informants consisting of one school principal and two classroom teachers. Data were gathered through structured interviews, allowing for in-depth exploration of participants’ experiences and perceptions. Analysis was conducted using the Miles and Huberman interactive model, involving data reduction, data display, and conclusion drawing to ensure the credibility and reliability of the findings.The results reveal that educational supervision is systematically implemented twice a year, guided by a well-structured plan that outlines objectives, schedules, and targeted competencies. The principal applies a collaborative supervision approach, using classroom visitation techniques to observe teaching practices in real contexts. Post-observation, constructive feedback sessions are conducted to highlight strengths, identify areas for improvement, and provide practical recommendations for pedagogical development. Teachers demonstrate notable progress in preparing lesson plans, delivering interactive learning activities, and applying effective evaluation methods. However, certain aspects such as the integration of technology in teaching and differentiation strategies still require further enhancement. The findings indicate that educational supervision not only improves technical teaching skills but also fosters teacher professionalism, boosts work motivation, and promotes a culture of continuous improvement within the school. The study underscores the importance of consistent, supportive, and developmental supervision in elevating instructional quality. It concludes that systematic and ongoing educational supervision represents a highly effective strategy for advancing teacher performance in elementary education. This research enriches the body of literature in educational management and provides practical implications for strengthening school leadership, particularly in rural and resource-limited contexts such as East Nusa Tenggara.